2022
DOI: 10.1111/bjh.18386
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control and seven‐year longitudinal neurocognitive study of adults with sickle cell disease in Ghana

Abstract: Sickle cell disease (SCD), an inherited blood disorder that is the most common genetic disorder worldwide, primarily affects people of African descent. [1][2][3] The SCD genetic polymorphism produces mutant haemoglobin molecules that polymerize within the erythrocyte during deoxygenation, resulting in sustained haemolytic anaemia and painful vaso-occlusive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…This study was conducted prior to the introduction of disease-modifying therapies, e.g., hydroxyurea. A Ghanaian study in adults aged 18–50 years with follow-up data after 7 years found a significant decline in verbal, non-verbal and global PIQ on the Revised Quick Cognitive Screening Test, as well as significant decreases in visuospatial abilities, processing speed, and EF ( 28 ). The rarity of these types of longitudinal evaluations in high and low resource countries is in part due to the logistical difficulties and expense.…”
Section: Introductionmentioning
confidence: 99%
“…This study was conducted prior to the introduction of disease-modifying therapies, e.g., hydroxyurea. A Ghanaian study in adults aged 18–50 years with follow-up data after 7 years found a significant decline in verbal, non-verbal and global PIQ on the Revised Quick Cognitive Screening Test, as well as significant decreases in visuospatial abilities, processing speed, and EF ( 28 ). The rarity of these types of longitudinal evaluations in high and low resource countries is in part due to the logistical difficulties and expense.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with sickle cell disease (SCD) experience progressive neurocognitive dysfunction resulting from cerebrovascular disease 1 , 2 and environmental disparities. 1 , 3 , 4 In 2020, the American Society of Hematology (ASH) published guidelines outlining the standard care for the prevention, diagnosis, and treatment of cerebrovascular disease in SCD, based on a systematic review of the literature and expert panel consensus. 5 Recommendations 8 and 9 describe guidance pertaining to screening and interventions to address cognitive deficits, respectively.…”
mentioning
confidence: 99%